2013
DOI: 10.1371/journal.pone.0070119
|View full text |Cite
|
Sign up to set email alerts
|

Is Bone Tissue Really Affected by Swimming? A Systematic Review

Abstract: BackgroundSwimming, a sport practiced in hypogravity, has sometimes been associated with decreased bone mass.AimThis systematic review aims to summarize and update present knowledge about the effects of swimming on bone mass, structure and metabolism in order to ascertain the effects of this sport on bone tissue.MethodsA literature search was conducted up to April 2013. A total of 64 studies focusing on swimmers bone mass, structure and metabolism met the inclusion criteria and were included in the review.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 99 publications
10
84
1
2
Order By: Relevance
“…12 Among swimmers, greater weekly quantity of training hours was related to lower BMC in the whole body (excluding the head). Long periods of training performed under conditions of hypogravity and the inflammatory response to exercise might support our findings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…12 Among swimmers, greater weekly quantity of training hours was related to lower BMC in the whole body (excluding the head). Long periods of training performed under conditions of hypogravity and the inflammatory response to exercise might support our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding this issue, there have been divergences in the scientific literature. Gómez-Bruton et al 12 suggested that increased bone mass at other specific sites directly stressed by sports participation, even without a clear biological pathway, is related to lower skull bone mass. In contrast, our findings showed that even after controlling for potential confounders, not only did swimmers have a higher percentage of overall BMC in the skull (no difference between the soccer/basketball and no-sport groups), but also they had a higher percentage of overall BMC in their upper limbs than the soccer/basketball players and the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, health professionals should select a strategy that enables assessments of lean mass and fat mass at regular intervals to discern whether changes in body composition suggest successful (e.g., gradual increases in muscle to fat ratios) or unsuccessful (e.g., gradual decreases in muscle to fat ratios) eating and exercise behavior. Although there has been concern that swimming occurs a zero-gravity environment lacking the ballistic stimulation of the skeleton seen in other sports, there is no evidence to suggest that healthy swimmers are at higher risk of low BMD than athletes participating in other sports (Gómez-Bruton et al, 2013).…”
Section: Assessment Of Body Compositionmentioning
confidence: 99%
“…Os efeitos do exercício aeróbico aquático na densidade mineral óssea ainda são bastante controversos em função da ausência de cargas compressivas durante sua execução (Gómez-Bruton et al, 2013). Em pessoas saudáveis, parece que a natação pode melhorar o metabolismo ósseo e a DMO em regiões específicas dos membros inferiores e superiores (Dook et al, 1997;Magkos et al, 2007;Maimoun et al, 2013).…”
Section: Fabio Bessa Melo De Souzaunclassified